Protection of the Rights of War Refugee Children under Martial Law - Mashkina, Olga (Theory and Practice of Public Administration, 2022)
The subject of special attention of the executive authorities should be the children from the families that were evacuated abroad. Recurrent monitoring visits to the places of their compact stay in the EU countries by representatives of the secretariat of the Ombudsman of Ukraine, the authorized adviser to the President of Ukraine on children’s rights and children’s rehabilitation, and people’s deputies were practical steps to ensure the interests of Ukrainian war refugee children. The financial, social, and psychological conditions of Ukrainian families staying in the EU are not the same. The satisfaction of children’s needs is also influenced by the level of financial support for refugee families, which is the highest in Germany and Poland. The composition, material condition, socio-professional prospects and life strategies of each of these families are different and require a differentiated approach. The educational rights of refugee children are met at a high level. They have the opportunity to go to kindergartens and study in schools of host countries, to attend extracurricular education institutions. The host countries have created all the conditions for children’s adaptation, language learning, and gradual integration into the local educational environment. Among the factors that determine children’s satisfaction with educational services are: the distance of the school from the place of residence; the quality of teaching the language of the host country; the presence of the so-called «integration class»; the presence of Ukrainian peers, etc. It is also beneficial that the Cabinet of Ministers of Ukraine has created special conditions for students who combine studies in foreign and Ukrainian schools. One of the most problematic components is the struggle for the rights of those children who ended up on the territory of the aggressor country. As of November 2022, according to official data alone, more than 11,000 Ukrainian children were deported to the aggressor country. Making rapid changes to Russian legislation, the authorities are trying to legalize and legitimize the processes of adoption of children from Ukraine by citizens of the Russian Federation, thereby trying to undermine the effect of Articles 15 and 50 of the Geneva Convention of 1949. Such criminal activity poses a particular danger for orphans and children deprived of parental care. Another risk group is children whose parents, for various reasons, accepted Russian citizenship, the acquisition of which was deliberately simplified for Ukrainians in recent years by the authorities of the aggressor country. It is obvious that it is extremely difficult to stop these illegal actions before the de-occupation of the territory of Ukraine is completed, but it is necessary to keep as accurate an account of such children as possible, involving all interested international institutions in this process.